2007
DOI: 10.15837/ijccc.2007.2.2345
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Wastewater Treatment Plant for Monitoring and Control Purposes by State – Space Wavelet Networks

Abstract: Most of industrial processes are nonlinear, not stationary, and dynamical with at least few different time scales in their internal dynamics and hardly measured states. A biological wastewater treatment plant falls into this category. The paper considers modelling such processes for monitorning and control purposes by using State -Space Wavelet Neural Networks (SSWN). The modelling method is illustrated based on bioreactors of the wastewater treatment plant. The learning algorithms and basis function (multidim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Stability conditions expressed in terms of network parameters were derived for neural networks in, e.g., (Sanchez and Perez, 1999;Kulawski and Brdyś, 2000;Nguyen and Brdyś, 2006). This is still under research for our SSWN, for which stability was demonstrated by simulation for a wide range of the parameter values in (Borowa et al, 2007). Let us denote the initial state discharge time by J.…”
Section: Training Of the Sswnmentioning
confidence: 99%
See 4 more Smart Citations
“…Stability conditions expressed in terms of network parameters were derived for neural networks in, e.g., (Sanchez and Perez, 1999;Kulawski and Brdyś, 2000;Nguyen and Brdyś, 2006). This is still under research for our SSWN, for which stability was demonstrated by simulation for a wide range of the parameter values in (Borowa et al, 2007). Let us denote the initial state discharge time by J.…”
Section: Training Of the Sswnmentioning
confidence: 99%
“…This is done by using historical data and searching for parameters values such that the corresponding prediction error is minimal. The procedure is called network training (Zhang et al, 2007;Borowa et al, 2007). The SSWN structure and its optimised parameters for one session ahead prediction are illustrated in Fig.…”
Section: Training Of the Sswnmentioning
confidence: 99%
See 3 more Smart Citations